2010
DOI: 10.1111/j.1439-0388.2010.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and fine mapping of quantitative trait loci for bone traits on chicken chromosome one

Abstract: In broiler chickens, bone problems are an important welfare issue that has been linked to genetic selection for rapid growth. The objectives of this study were to identify and fine map quantitative trait loci (QTL) associated with bone traits. The Northeast Agricultural University resource population (NEAURP) being an F(2) population was used in this study, and a total of 17 bone traits were measured. In primary genome scan, the linkage map was constructed with 23 microsatellite markers across the entire chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
20
1
1
Order By: Relevance
“…2008) and the QTL was located near the microsatellite marker ADL328. The QTL for BW from 4 to 12 weeks of age and CW at 12 weeks of age was the same as the QTL for bone traits, including metatarsus length (MeL) and metatarsus circumference (MeC) at 4, 6, 8, 10 and 12 weeks of age and keel length (KeL) and metatarsus claw weight (MeCW) at 12 weeks of age, that was reported by Zhang et al. (2010) using the same F 2 population.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…2008) and the QTL was located near the microsatellite marker ADL328. The QTL for BW from 4 to 12 weeks of age and CW at 12 weeks of age was the same as the QTL for bone traits, including metatarsus length (MeL) and metatarsus circumference (MeC) at 4, 6, 8, 10 and 12 weeks of age and keel length (KeL) and metatarsus claw weight (MeCW) at 12 weeks of age, that was reported by Zhang et al. (2010) using the same F 2 population.…”
Section: Introductionmentioning
confidence: 54%
“…A QTL with pleiotropic effects on BW and bone traits was mapped and fine‐mapped near the marker ADL328 (Liu et al. 2007, 2008; Zhang et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (2010) studied bone traits and identified 12 QTL between LEI0079 and ROS0025 markers on GGA1. In the current study, we mapped a QTL region for tibia width and weight between the LEI0079 and MCW145 markers on GGA1.…”
Section: Quantitative Trait Loci Mappingmentioning
confidence: 99%